Scope and Utility of Micro-morphological Markers in Hybridity Testing of Tomato (Solanum lycopersicum L.) - CHENNEM KIRAN KUMAR REDDY; SUDHEER KUMAR JAIN; MB ARUNKUMAR; S GOPALAKRISHNAN; AWANI KUMAR SINGH; ZAKIR HUSSAIN (Seed Research, 2026)
Conventionally, grow-out-test, the only official method of genetic purity testing, is season dependent, labour intensive; and locks huge investment. Alternatives needed to be developed to test the genetic purity of a given seed lot in a shortest possible time. To bridge the above gap, the present study was undertaken to identify the four hybrids and their parental lines (six) in tomato using micro-morphological markers at seedling stage. Among the various micro-morphological characters: anthocyanin pigmentation pattern on midrib of cotyledonary leaf, shape of cotyledonary leaf in cross section, shape of first leaf blade, blistering pattern and positioning of veins on the lamina of first leaf, identified as new characters; reported as first of its kind in hybridity testing of tomato, which are easy and cost-effective. The shape of cotyledon and anthocyanin pigmentation on lower surface of first leaf were also identified as first of their kind in tomato for parental lines identification.